2019
DOI: 10.21613/gorm.2018.775
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Inflammatory Markers in Gestational Diabetes Mellitus

Abstract: <p><strong>Objective:</strong> Gestational diabetes mellitus is a common disorder of carbohydrate metabolism, with onset or first recognition during pregnancy, resulting in hyperglycemia of variable severity. Insulin resistance and chronic subclinical inflammation are the underlying mechanisms of the disease. Soluble interleukin-2 receptor, neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio are the markers of inflammatory disease processes such as type 1 and 2 diabetes mellitus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…However, Sjaarda et al (2018) tested the inflammatory status by high-sensitive C-reactive protein (hs-CRP) and found that low-grade inflammation is very common (20-40%) in reproductive-age women, including normal-weight women. Apart from hs-CRP, systemic inflammatory status could be assessed by NLR, MLR, and PLR ( Mertoglu et al, 2019 ; Madendag et al, 2018 ) . On the other hand, platelets release a high rate of inflammatory mediators to the environment during inflammation ( Thomas & Storey, 2015 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, Sjaarda et al (2018) tested the inflammatory status by high-sensitive C-reactive protein (hs-CRP) and found that low-grade inflammation is very common (20-40%) in reproductive-age women, including normal-weight women. Apart from hs-CRP, systemic inflammatory status could be assessed by NLR, MLR, and PLR ( Mertoglu et al, 2019 ; Madendag et al, 2018 ) . On the other hand, platelets release a high rate of inflammatory mediators to the environment during inflammation ( Thomas & Storey, 2015 ) .…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] However, the results are contradictory as there are numerous studies that reported no difference in these parameters. [10,[14][15][16][17] Similarly, there are contradictory results with respect to WBC and red blood cells. [13,16] Among platelet indices only PCT was found to be increased significantly in GDM patients; however, in regression analysis this association disappeared indicating that PCT is not an independently associated factor.…”
Section: Discussionmentioning
confidence: 99%
“…[10,[14][15][16][17] Similarly, there are contradictory results with respect to WBC and red blood cells. [13,16] Among platelet indices only PCT was found to be increased significantly in GDM patients; however, in regression analysis this association disappeared indicating that PCT is not an independently associated factor. PMI was also assessed which had not been assessed in GDM before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated serum hs-CRP is an independent risk factor for cardiovascular disease. However, the relationship between inflammatory response and GDM remains unclear [6].…”
Section: Introductionmentioning
confidence: 99%